Ad-Din from the Epistemological Perspective of the Qur'an - Husein, Muhammad; Muzakkir, Muzakkir; Rambe, Uqbatul Khair (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Is ad-din indeed exclusively viewed as a religion (belief)? And how about religion (belief) be marginalized from human life? Is there another meaning of ad-din from the perspective of epistemology Qur'an? What is the meaning of the term ad-din in the Qur'an? Departing from these academic questions that will try to be answered and examined in this study based on valid reference sources (sahih) through the works of authoritative scholars. Furthermore, this type of research is a literature study with a model of semantic study approach that is combined thematically, then using descriptive qualitative research methods. So the author found, that the meaning of ad-din in the perspective of the Qur'an is very deep so it is not appropriate if separated from the scope of life because it is a guide to the way of life of humans in the form of systems, laws, obedience, submission, trust, and others which shows that the meaning of ad-din is very broad. Four verses in the Holy Quran describe a religion (Hanifan, Islam, Millah, and ad-din). Ad-din can mean religion, the last day, the day of retribution and obedience. Thus, through an effort to understand the meaning of the ad-din perspective of the epistemology Qur'an can realign life in the world properly and correctly.